The contribution of successional grasslands to the conservation of semi-natural grasslands species – A landscape perspective. (February 2017) - Schmid, Barbara C.; Poschlod, Peter; Prentice, Honor C.
Abstract: Many species that are typical of calcareous, semi-natural grasslands ("typical grassland species") are declining in Europe as a result of habitat-loss and -fragmentation. Whereas populations of these species are expected to be largest in old semi-natural grasslands, these species may also occur in successional grasslands on previously arable fields. We used a space-for-time approach to analyse changes in the frequencies of typical grassland species, and changes in soil properties, over a 280-year arable-to-grassland succession within a Swedish landscape. Our study revealed that a number of typical grassland species had higher frequencies in mid-successional (50–279 years) than in old (≥ 280 years) grasslands. Mid-successional grasslands also contained many of the typical grassland species that were present in old grasslands, but at lower frequencies, and had soil conditions similar to those of old grasslands. Early-successional (5–14 and 15–49 years) grasslands contained few typical grassland species. In highly fragmented landscapes, mid-successional grasslands provide additional habitat for many typical grassland species, and can function as temporary refugia ("substitute habitat") for these species until old grasslands are "restored". The overall population sizes of some typical grassland species and red-listed species are likely to be substantially increased by the presence of mid-successional grasslands within the landscape. Our study suggests that, rather than focussing solely on old grassland fragments, conservation strategies for typical grassland species should adopt a dynamic, landscape-based perspective that recognizes the role of successional grasslands. Ensuring a continuous development of mid-successional grasslands is expected to be beneficial for populations of many typical grassland species. Highlights: Some typical grassland species have their highest frequencies in successional stages. Mid-successional grasslands augment population sizes of typical grassland species. Grassland conservation strategies should recognize the role of successional processes. Grassland conservation strategies should adopt a dynamic, landscape-based perspective.